If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2w + 7 = 3x + -3 Reorder the terms: 7 + -2w = 3x + -3 Reorder the terms: 7 + -2w = -3 + 3x Solving 7 + -2w = -3 + 3x Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -2w = -3 + -7 + 3x Combine like terms: 7 + -7 = 0 0 + -2w = -3 + -7 + 3x -2w = -3 + -7 + 3x Combine like terms: -3 + -7 = -10 -2w = -10 + 3x Divide each side by '-2'. w = 5 + -1.5x Simplifying w = 5 + -1.5x
| 12-58= | | 27+1x=23 | | 5x-(12-2x)=3x | | 7.3x-1.8=20.1 | | -b=72 | | -1x+28=18 | | 10x+180=(x+10)(x+4) | | 66y=132 | | -26+5x=24 | | 21=5m+6+5 | | 12x-2=150 | | 5h-7=12(h+1) | | 72+-5x=27 | | 3k+6.2= | | 9=30n | | x*-6=4 | | 850=1.33*x | | (8y-15)2/3=14 | | 7/5/3 | | 1061=1.71*x | | 2(h+10)=59 | | h(t)=-16t^2+32x+1.5 | | -16r=-75 | | 4/5x-1/10x=9/10x | | 5t-3=(t+7)+3t | | 2x^3-x^2+16x-9=0 | | (2x)+(x)=162 | | 48+(8x+20)=180 | | 25.0=0.520d+14.7 | | t+16.7=-49 | | 1/4q=6 | | 2+4=-(-7x+6) |